La pratique de la jachere en Afrique tropicale: ccomparee au Nigeria et au Cameroun - Nkamleu, G.B.; Kamajou, F.; Gockowski, J. (2000)
In sub-Saharan Africa, intensification of agriculture and rational use of arable land are essential for long-term growth (Gros, 1979, Johnston, 1990, Oluf et al., 990). Extensive cultivation methods and the population explosion are pushing the limits of cultivated land every day; deforestation accelerates; the productive capacity of the land is reduced